1997
DOI: 10.1093/ajcn/66.2.254
|View full text |Cite
|
Sign up to set email alerts
|

Influence of n-3 fatty acid supplementation on the endogenous activities of plasma lipases

Abstract: The aim of these studies was to explore the possibility that enhanced triacylglycerol clearance may contribute to the hypotriacylglycerolemic effect of n-3 fatty acids in humans. Healthy subjects (n = 20) and hypertriacylglycerolemic patients (n = 6) were given a placebo (olive oil, OO) or a fish-oil concentrate (FOC; 41% eicosapentaenoic acid and 23% docosahexaenoic acid) in two, independent, randomized, blind trials. For the healthy subjects, the FOC treatment period was 3 wk long and FOC intakes were 5 g/d.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
77
1
3

Year Published

1999
1999
2014
2014

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(90 citation statements)
references
References 53 publications
8
77
1
3
Order By: Relevance
“…In addition, the release of LPL after heparin administration represents a single point, unphysiological stimuli. The negative correlation between PHLA and TAG-AUC, in the present study, ®ts with the ®ndings of Harris et al (1997) comparing LPL activity and fasting TAG levels. The relationship between PHLA and TAG-AUC suggest that PHLA levels re¯ect recent exposure to the substrate, plasma TAG, with the result that high levels of activity effectively clear TAG from the plasma.…”
Section: Lpl In Human Adipose Tissue MC Murphy Et Alsupporting
confidence: 89%
See 1 more Smart Citation
“…In addition, the release of LPL after heparin administration represents a single point, unphysiological stimuli. The negative correlation between PHLA and TAG-AUC, in the present study, ®ts with the ®ndings of Harris et al (1997) comparing LPL activity and fasting TAG levels. The relationship between PHLA and TAG-AUC suggest that PHLA levels re¯ect recent exposure to the substrate, plasma TAG, with the result that high levels of activity effectively clear TAG from the plasma.…”
Section: Lpl In Human Adipose Tissue MC Murphy Et Alsupporting
confidence: 89%
“…In addition, we have shown that ®sh oils stimulate and activate LPL; human volunteers had signi®cantly raised post-heparin LPL activity when fed a ®sh oil-containing meal compared with a mixed oil meal when measured 12 h after the meal was consumed (Zampelas et al, 1994). This work has recently been con®rmed by the ®ndings of Harris et al (1997). We have also shown signi®cantly increased LPL gene expression in rat epididymal adipose tissue following a ®sh oil diet (Murphy et al, 1993).…”
Section: Introductionsupporting
confidence: 57%
“…Decreased VLDL particle number would conceivably lead to a greater proportion of VLDL being converted into LDL. Moreover, these effects may entail enhanced lipolysis via the stimulation of lipoprotein lipase activity, as reported elsewhere (38).…”
Section: Regulation Of Apolipoprotein B Kineticsmentioning
confidence: 53%
“…A limited number of human studies have generally failed to show an increased postheparin LPL activity with high fish oil diets, 17,18,56,59 although 2 recent reports have found significant increases. 60,61 Zampelas et al 60 have shown elevated postheparin LPL activity 9 hours after meals enriched with n-3 PUFA compared with saturated fatty acid, and Harris et al 61 observed a 62% increase in endogenous LPL activity in healthy volunteers after 3 weeks of fish oil supplementation (5 g/d). Several mechanisms may be responsible for this observed increase in LPL activity, including changes in LPL gene expression, transport of newly synthesized LPL to the vascular wall, or a change in NEFA metabolism.…”
Section: Discussionmentioning
confidence: 99%